Graduate students' research-based learning experiences in an online Master of Education program - Jacobsen, Michele; McDermott, Mairi; Brown, Barbara; Eaton, Sarah Elaine; Simmons, Marlon (Journal of University Teaching and Learning Practice, 2018)
The purpose of this research was to better understand graduate students' learning experiences in a research-intensive, online Master of Education (MEd) program. In alignment with the program goal for graduate scholars of the profession, this course-based program adopted an inquiry-based signature pedagogy grounded in the innovative practice of research-based learning. As part of this study, we explored broader program structures, including the cohort-based model, course sequencing and research ethics approval processes, which situate the research-based learning experiences. Several research questions framed our investigation into the experiences of online students who are engaged in a research-active MEd program. Analysis of survey and focus group information contributes to this mixed-methods case study and provides insights into implications for research-based learning in online course-based graduate programs.